2018
DOI: 10.1002/jctb.5692
|View full text |Cite
|
Sign up to set email alerts
|

A review on the advances in nitrifying biofilm reactors and their removal rates in wastewater treatment

Abstract: Growing demand for efficient wastewater treatment systems is spurring on the development of new technologies. Biofilm‐based reactors can be used for the treatment of a variety of wastewaters and these reactors are resistant to toxic environments. Bioreactors, such as sequencing batch biofilm and moving bed biofilm are advanced techniques to treat various types of wastewaters with diverse operating conditions. Ammonium oxidizing bacteria, nitrite oxidizing bacteria and Anammox (anaerobic ammonium oxidation) bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 135 publications
0
15
0
Order By: Relevance
“…Previous evaluation of facility nitrogen removal has shown that the nitrifying towers experience large seasonal variations in ammonia loading due to the partial nitrification that occurs within the activated sludge process during the warmer months. Consequently, when this activity declines in the winter, the towers are met with the challenge of accepting larger amounts of ammonia at a time when the growth of AOB and NOBs to convert this load are at their least efficient (Chaali, Naghdi, Brar, & Avalos‐Ramirez, 2018). This has led to the colder months (December–March) having higher average historically higher nitrogen discharges.…”
Section: Resultsmentioning
confidence: 99%
“…Previous evaluation of facility nitrogen removal has shown that the nitrifying towers experience large seasonal variations in ammonia loading due to the partial nitrification that occurs within the activated sludge process during the warmer months. Consequently, when this activity declines in the winter, the towers are met with the challenge of accepting larger amounts of ammonia at a time when the growth of AOB and NOBs to convert this load are at their least efficient (Chaali, Naghdi, Brar, & Avalos‐Ramirez, 2018). This has led to the colder months (December–March) having higher average historically higher nitrogen discharges.…”
Section: Resultsmentioning
confidence: 99%
“…In the available body of literature, we may find several sources describing the positive effect of barbotage reactor filling on liquid aeration. Results of some research papers [5,75] showed that the above-mentioned aspect is still ambiguous. Kalenik et al [76] carried out a study on a tubular aerator filled with a moving bed of Białecki rings.…”
Section: Influence Of Moving Bed On System Aerationmentioning
confidence: 99%
“…Nitrogen forms in wastewaters are a major concern, especially in sensitive areas, where they have to be removed through biological treatment, i.e. specifically designed activated sludge configurations, before discharge into receiving waters . Now, it is well known that biological nitrogen removal requires a sequence of steps involving ammonification – hydrolysis of organic nitrogen, nitrification – oxidation of ammonia and denitrification – removal of oxidized nitrogen that serves as final electron acceptor for organic matter under anoxic conditions .…”
Section: Introductionmentioning
confidence: 99%
“…specifically designed activated sludge configurations, before discharge into receiving waters. 1,2 Now, it is well known that biological nitrogen removal requires a sequence of steps involving ammonification -hydrolysis of organic nitrogen, nitrification -oxidation of ammonia and denitrification -removal of oxidized nitrogen that serves as final electron acceptor for organic matter under anoxic conditions. 3,4 These steps are best achieved in single sludge systems including heterotrophic and autotrophic biomass fractions with the ability to switch and sustain specific metabolic activities under a succession of aerobic/anoxic conditions.…”
Section: Introductionmentioning
confidence: 99%